Quality indicators in nutritional therapy: analysis of the evolution of post-implantation service (Research, Society and Development, 2021)
Introduction Quality Indicators in Nutrition Therapy (IQTN) are important tools for evaluating and monitoring the quality of Nutrition Therapy, as they identify possible difficulties and failures related to nutritional care and enable early intervention. Objective To evaluate the implementation of Quality Indicators in Nutritional Therapy in the Nutritional Therapy service of the University Hospital of Sergipe. Methodology Observational retrospective study carried out with data on the daily score of Quality Indicators in Nutritional Therapy (IQTN) of adult and elderly patients, of both sexes, undergoing Enteral Nutritional Therapy (ENT) and/or Parenteral Nutritional Therapy (NPT) for at least 72 hours. Twelve IQTN were analyzed in two moments: first month and 12 months after implantation. The goals recommended by the International Life Sciences Institute (ILSI) of Brazil were used and the moments were compared by the Wilcoxon test with a significance level of p≤0.05. Results and discussion It was demonstrated that of the 12 IQTN, 6 did not reach the goals at the beginning and surpassed them at the end of the study; 1 improved, despite remaining below the target in both moments (p = 0.012); and the other indicators remained within the recommended goals throughout the study. The significant improvement in the frequency of indicators demonstrates the optimization of nutritional care and better quality of care for patients in Nutritional Therapy. Conclusion It was demonstrated through the analysis of the implementation of the IQTN that there was a significant evolution in the nutritional therapy service of the evaluated university hospital.